Security Enhancement for Mobile Ad Hoc Network Using Region Splitting Technique. Issue 2 (2nd April 2016) - Kumar, P. Mohan; Gopalakrishnan, S.
ABSTRACT: Mobile Ad hoc Network (MANET) is more vulnerable to various attacks since it has no centralized or any pre-existing network structure. In this research, we proposed an Attacker Identification using Region Splitting (AIRS) scheme for intrusion detection and attacker identification in MANET. In this scheme, the network is split into several regions for efficient detection. Our proposed AIRS scheme provides an effective response for attacks such as: jellyfish attack, neighbor attack, and location disclosure attack. Here, we calculate Degradation Performance (DP) and Trust of Attack and it provides three response schemes such as Full isolation, Partial isolation, and No reaction. We compare our proposed scheme with the existing Secure Routing Attacker Identification (SRAI) approach. Experimental results show the performance of response scheme on jellyfish attack, neighbor attack, and location disclosure attacks on various scenarios.